Association of zinc and copper with clinical parameters in the preterm newborn. Issue 11 (24th October 2017) - Kojima, Chiharu; Shoji, Hiromichi; Ikeda, Naho; Kitamura, Tomohiro; Hisata, Ken; Shimizu, Toshiaki
Abstract: Background: Given that preterm infants are born at a time of rapid fetal growth, they are at risk of deficiency of essential nutrients for brain development, including zinc (Zn) and copper (Cu). This study evaluate the relationship between serum Cu or Zn, gestational age (GA) and anthropometric parameters at birth in preterm infants. Methods: This was a retrospective study of infants <35 weeks' GA from January 2010 to August 2012. We collected the data from medical records of 59 preterm infants at birth with regard to GA, anthropometric parameters, and serum Cu and Zn levels. Correlation of Cu, Zn, and GA with anthropometric parameters at birth was then done. Results: Zn was inversely correlated with GA, bodyweight (BW), body length (BL), and head circumference (HC), and Cu was inversely correlated with the standard deviation (SD) score for BW, BL, and HC. On stepwise multiple regression analysis, GA was a significant independent predictor of Zn level, and HC SD score was a significant independent predictor of Cu level. Conclusions: Prematurity influences Zn, and intrauterine head growth restriction influences Cu at birth in preterm infants. Further research is needed to evaluate the relationship between intrauterine growth restriction and brain Cu metabolism.